Vesicolithotomy in 64 Year-Old Male with Giant Bladder Stone at Leona Hospital, Kupang, East Nusa Tenggara, Indonesia - Telussa, Arley Sadra; Djungu, Epafroditus M.K; Mawikere, Stevanikov J.M. (Universitas Nusa Cendana, 2023)
Giant bladder stone is a rare case of urinary tract stones. These cases are strongly related to social economy status. The patient was a 64 year old male with bladder stone with the size of 10,5 cm x 7,5 cm. The patient presented to emergency department with pain on lower abdomen due to severe lower urinary tract symptoms. A hard mass was palpable in suprapubic area. Cystoscopy was performed, followed by vesicolithotomy. Conclusion : Giant bladder stone can be treated by vesicolithotomy preferably following cystoscopy procedure to eliminate the possibility of bladder mass.